Inovasi IoT: Alat dehidrasi bioetanol dari limbah bonggol jagung untuk energi terbarukan - Pitrianti, Destica; Naiya, Rara Weinita; Ramadavini, Miftah Azzura (Jurnal Teknologi Cerdas, 2025)
Mardiharjo Village, Musi Rawas Regency, is facing the issue of corn cob waste that is not being utilized optimally and is polluting the environment. Corn cobs contain cellulose and hemicellulose, which have the potential to be processed into bioethanol. This research aims to design an IoT-based bioethanol dehydration device that can purify bioethanol to a concentration of 99%, in accordance with fuel standards. This device is equipped with a dehydration column, heater, condenser, and automatic control using a microcontroller. IoT technology enables real-time temperature monitoring for energy efficiency. The design was created using Tinker software and thoroughly documented. This innovation is expected to open up opportunities for utilizing corn waste as renewable energy and an environmental solution in the agricultural sector.